Reforma trabalhista de 2017: análise quantitativa e qualitativa dos aspectos processuais e da conflituosidade em geral. - Ivo, Jasiel (2022)
This work is an analysis of the effects of the 2017 Brazilian labor law reform in its procedural aspect. It is structured in two distinct parts or sections. In the first, entitled "From the beginnings of work to contemporaneity: a brief tour of the history of human work", which constitutes the first chapter, an inventory of human work throughout history and within the scope of Western society is made, a kind of journey through the most significant stages, advances and setbacks, until the arrival of today, when technological innovations erode jobs and the economic model further undermines these relationships, reconfiguring work itself. This perspective is considered relevant because it makes no sense to study law if the objective is not to comprehend human conduct, understanding the law in the environment and context in which the labor reform in Brazilian law has been taking place. Introduced in the legal system through Law No. 13,467 of July 13, 2017, it entered into force on November 11, 2017 and promoted intense changes both in material labor law and in procedural labor law. In the second section (or part 2) of the thesis, access to justice is studied, with the identification of the main obstacles to its fulfillment, the renewal of labor procedural law and the new approaches that should be given to this principle, moving on to an understanding of due process, in its procedural and substantive dimensions, leading up to the link between access to justice and due process, from the perspective of fundamental rights. The modifications performed by the reforming law are analyzed, especially in regards to the wording of § 1 of article 840 of the Consolidation of Labor Laws - CLT, which demands that the statement of claims in procedural labor law be offered formulating a certain request, determined and with indication of its value immediately and, if the requests do not meet the requirements of § 1, § 3 of the same consolidated provision, added by the same law, it determines that they are to be dismissed. The reform also changed the methodology for charging court fees in the event of the case being closed due to the absence of the claimant, and it also imposed the collection of legal and expert fees in the event of the worker's loss of suit, even if he is a beneficiary of free and full legal assistance. It is investigated whether there was a violation of access to justice and substantial due process, since the themes generated various questions, both from the academic point of view, raising the problem and raising the hypotheses, as well as from a pragmatic perspective, because even after four years after the law has been in force, several actions are still pending in the Supreme Court - STF, through the concentrated review of constitutionality, in addition to the consistent questioning in terms of diffuse control, before the Labor Court, which will reach the STF through extraordinary appeal. Through the hermeneutic-analytical method, the research crosses two major areas of Law: the constitutional and the procedural. From these branches, with special attention to procedural labor law, the study of access to justice and due process in the Brazilian labor law reform of 2017 is carried out.